Determinants of budget forecast errors and their impacts on budget effectiveness: evidence from Indonesia - Baldric Siregar; Lilis Susanti (Journal of Economics, Business, and Accountancy Ventura, 2018)
This research attempts to identify the determinants of budget forecast errors and explore the impact of the errors on the budget effectiveness. This study differs from the earlier studies such as including covering 90% of districts and cities, other studies on budget forecast error have not addressed how financial and governmental characteristics effect budget forecast error, and using a structural model to test the factors effecting budget forecast error and their impacts on budget effectiveness. The data are derived from Central Bureau of Statistics and local government website. It used the data of 444 local government for the period of 2006 to 2013, and analyzed them using a partial least square for testing the hypotheses. The results show that the significant factors affecting budget forecast errors are revenue growth, expenditure growth, and government complexity. The higher the revenue growth the greater the likelihood of budget forecast errors. Likewise, the greater the spending growth, the greater the budget forecast errors. The empirical evidence also suggests that budget forecast errors are bad for the economy. The implications of this findings are that local government must be more careful in projecting a growing income and expenditure budget, coordinate well so that work units can develop accurate budgets, and carry out a better monitoring function for all the main stages of budgeting.